Mediation Approach : Strategi Kepala Sekolah dalam Manajemen Konflik di Lembaga Pendidikan - Ruqoiyah, Ruqoiyah (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
Challenges of Indonesian society, especially for millennials is the strengthening of digital literacy and filtering of information. Users of communication technology such as smartpone need to be balanced with the right insight and understanding of the influence of the use of communication media. Smart communication media (smartpone) that is equipped with the latest features and high-ability should be held by smart people, namely people who can make use of the media properly and wisely. The school is a place to develop students' potential with the teaching and learning process conducted on a periodal and structured basis. In schools there is also the potential for conflict between students, students with teachers, and teachers with parents (parents). Conflict can be defined by dispute or conflict. School institutions or teachers are often scapegoats for the attitudes and behaviors of naughty students, generally parents in responding to their child's misbehavior is too excessive, they seem to wash their hands and assume that teachers in schools are not right in educating. Parents in general pay less attention to the causes and consequences caused by the misbehavior of students in school, parents are more focused on excessive expression to lecture and lecture teachers in school because it is considered less because of educating students, this kind of thing can actually be found the best solution, one of which is through mediation approach. Research Method is a description research with a library approach. Based on the results of the analysis of data sources can be concluded that the mediation approach can be implemented in internal and external conflicts of educational institutions. The mediation approach is carried out in two stages. The first stage is detoral mediation, and the second stage is cross-sectoral mediation. The two stages are taken in sequence or orderly, in order to produce comprehensive information and conclusions.